Factors Affecting the Online Purchase Decision in the Nepalese Context - Manandhar, Raju Bhai; Dongol, Padam; Chalise, Dhan Raj; Manandhar, Eirika; Katwal, Milan (Nepal Journal of Multidisciplinary Research, 2025)
Background: Online shopping has made it simpler to purchase a wide variety of products and get them delivered directly to the doorsteps. It has been growing due to the expansion of Internet facilities and the busy schedule of people. The study was conducted to identify the influencing factors of online purchase decisions. Methods: The study was conducted among the 447 consumers living in the Kathmandu Valley. The study was based on the quantitative descriptive and explanatory research design. The study adopted the simple random sampling technique to select the respondent. Structured survey questionnaire was used to collect the data. Validity and reliability were ensured by measuring the Cronbach’s Alpha test (.825). Frequency distribution, mean, and regression are used to analyze the data. Results: Results show positive perceptions across key dimensions, including convenience, well-designed websites, time-saving, security, and diverse product variety in online shopping. However, there is room for improvement in after-sales service and product quality. The ANOVA results show a statistically significant relationship between convenience, product quality, and website (p < 0.001), and other predictors like security, after-sales services, and product varieties (p < 0.005). Conclusion: The overall positive sentiment, as indicated by the average mean score, underscores the favorable outlook of respondents towards the online shopping experience, providing businesses with insights into areas of strength and potential enhancement. Novelty: the study has statistically measured the effect of different factors on online purchase decisions. These insights can help businesses optimize online shopping experiences and drive consumer engagement.